Integrasi Pembelajaran Sosial Emosial Pada Pendidikan Agama Islam Dalam Pembentukan Akhlakul Karimah - Eddy Saputra (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Education is still the infrastructure for changing attitudes, especially when it is associated with Islamic religious education, an educational concept that emphasizes divine and human values. Lifelong learning seems to have no meaning when compared to the high number of crimes committed by most students, the moral values taught are also not left behind if one looks at the high deviant behavior that occurs among students. An independent curriculum with a student centered learning concept can be a breakthrough so that students are fully aware of the learning process, one of which is with social emotional learning, where learning that focuses on developing social and emotional competencies with the aim of students being able to understand and manage their emotions and be able to develop positive social skills, build healthy relationships and be able to make wise decisions can be integrated with Islamic religious education. This study uses a qualitative approach with a phenomenological methodology seeking an in-depth understanding of human phenomena from the perspective of the individuals who experience them. The research aims to integrate social-emotional learning with Islamic religious education as an effort to realize that the success of education is accompanied by positive changes in attitudes and personality of students who prioritize good morals in behavior.